2021
DOI: 10.1007/s11858-021-01315-5
|View full text |Cite
|
Sign up to set email alerts
|

The relation between creativity and students’ performance on different types of geometrical problems in elementary education

Abstract: Aim In the current study we aimed to investigate the relation between creativity and mathematical problem solving in the upper grades of elementary school. Methods To examine how student’s levels of general creativity were related to their performance on different types of geometrical problems, a geometry test with diverse problems was administered to a sample of 1665 Dutch students from third to sixth grade, as well as a creativity test. The geometry test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
(62 reference statements)
1
7
0
Order By: Relevance
“…The relationships of these variables can be summarized by the equation y=6.11+1.64x1+0.04x2, where y is the mathematics problem-solving performance of the participants and x1 and x2 are variables representing the self-efficacy and creativity of the participants, respectively. This result is parallel to the study of Schoevers, et. al.…”
Section: Discussionsupporting
confidence: 88%
“…The relationships of these variables can be summarized by the equation y=6.11+1.64x1+0.04x2, where y is the mathematics problem-solving performance of the participants and x1 and x2 are variables representing the self-efficacy and creativity of the participants, respectively. This result is parallel to the study of Schoevers, et. al.…”
Section: Discussionsupporting
confidence: 88%
“…The systematic review of the empirical research on creativity in mathematics (education) revealed that MSTs are the most frequently used research tool for the evaluation of MC at the school level. Examples of such studies can be seen in Assmus and Fritzlar (2022) and Schoevers et al (2022).…”
Section: 41mentioning
confidence: 99%
“…Skemp (1986) argued that "mathematical generalization is a sophisticated and powerful activity" (p. 58) and drew a connection between mathematical understanding and the ability to generalize. Schoevers et al (2022) argued that creativity predicted student performance on geometrical problems generally and that creativity predicted student achievement on geometry problems requiring multiple solutions. Focusing on patterns, Assmus and Fritzlar (2022) argue that mathematical activity offers a variety of opportunities for creative development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schoevers et al [4] investigated into the connection between mathematical problem-solving in elementary schools and creative thinking. There are four closed routine issues, six closed non-routine problems, and four open non-routine problems using geometry tests (multiple solution problems).…”
Section: Introductionmentioning
confidence: 99%